ANALISIS PENYUSUNAN MATERIAL DI WAREHOUSE PT XYZ - Kawidyasari, Warranty; Tarigan, Elsya Paskaria Loyda (LPPM Universitas Putera Batam, 2023)
Poor material preparation and untidy warehouse PT. XYZ causes difficulties for employees in picking up materials and long distances for picking up materials that have a high picking frequency. The arrangement of the material layout was redesigned to make it easier to pick up material and shorten the distance for picking up material. To improve the layout of the arrangement and tidiness of the warehousing, researchers use the ABC Classification and the application of 5S. The total distance in the initial layout is 2902 meters while the proposed layout is 2278 meters. OMH in the initial layout of Rp. 1,905,000.00 while the proposed layout is Rp. 1,685,706.00. So the total decrease in OMH is Rp. 219,000.00 / month and the distance efficiency obtained is 21.5% / month.